Solar Cell

By using graphene compounds containing iodine in solar cells and adding fluorobor-based compounds to the hole transport layer, the problem of insufficient photo durability of the solar cell is solved, and the stable performance of the hole transport layer under light is achieved.

JP7671752B2Active Publication Date: 2025-05-02PANASONIC HOLDINGS CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022532486
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-24
Filing Date
2021-06-02
Publication Date
2025-05-02
Estimated Expiration
2041-06-02

AI Technical Summary

Technical Problem

The light durability of existing solar cells is insufficient, especially due to the degradation of the performance of the hole transport layer due to the migration of iodine ions.

Method used

In the structure of the solar cell, a graphene compound containing iodine is added as the photoelectric conversion layer, and a fluorobor-based compound is added as an oxidant in the hole transport layer, while bromide, chloride or fluoride is used in the intermediate layer to prevent the migration of iodine ions.

Benefits of technology

The photo durability of solar cells is significantly improved and the stability of the performance of the hole transport layer under light is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671752000003
    Figure 0007671752000003
  • Figure 0007671752000004
    Figure 0007671752000004
  • Figure 0007671752000005
    Figure 0007671752000005
Patent Text Reader

Abstract

A solar cell 100 according to the present disclosure is sequentially provided with a first electrode 2, a photoelectric conversion layer 3, an intermediate layer 4, a hole transport layer 5 and a second electrode 6 in this order; the hole transport layer 5 contains a hole transport material and an oxidant; the photoelectric conversion layer 3 contains a perovskite compound that contains iodine; and the intermediate layer 4 contains at least one substance that is selected from the group consisting of bromides, chlorides and fluorides.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to solar cells. [Background technology]

[0002] Non-Patent Document 1 discloses a perovskite solar cell that uses a perovskite compound represented by CH3NH3PbI3 as a photoelectric conversion material, TiO2 as an electron transport material, and Spiro-OMETAD as a hole transport material. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] “Sequential deposition as a route to high-performance perovskite-sensitized solar cells”, Nature, vol.499, 18 July 2013, DOI:10.1038 / nature12340 [Non-Patent Document 2] “Ionic Reactivity at Contacts and Aging of Methylammonium Lead Triiodide Perovskite Solar Cells”, Adv. Energy Mater., 6: 1502246, DOI: 10.1002 / aenm.201502246 [Non-Patent Document 3] “Surface passivation of perovskite film for efficient solar cells”, Nature Photonics volume 13, pages460-466(2019) [Non-Patent Document 4] “An interface stabilized perovskite solar cell with high stabilized efficiency and low voltage loss”, Energy Environ. Sci., 2019, 12, 2192-2199 [Non-Patent Document 5] “Compositional engineering for thermally stable, high exceeding efficient perovskite solar cells 20% power conversion efficiency with 85 ℃ / 85% 1000h stability”, Adv. Mater. 2019, 31, 1806823 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a solar cell having high light durability. [Means for solving the problem]

[0005] The solar cell of the present disclosure comprises: A first electrode, a photoelectric conversion layer, an intermediate layer, a hole transport layer, and a second electrode, in this order, the hole transport layer comprises a hole transport material and an oxidant; The photoelectric conversion layer contains a perovskite compound containing iodine, and The intermediate layer includes at least one selected from the group consisting of bromide, chloride, and fluoride. Effect of the Invention

[0006] The present disclosure provides a solar cell having high light durability. [Brief description of the drawings]

[0007] [Figure 1]FIG. 1 shows a cross-sectional view of a solar cell according to a first embodiment. [Diagram 2] FIG. 2 shows a cross-sectional view of a modified example of the solar cell according to the first embodiment. [Diagram 3] FIG. 3 shows a cross-sectional view of a modified example of the solar cell according to the first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] (Findings on which this disclosure is based) Perovskite solar cells use perovskite-type crystals represented by ABX3 (A is a monovalent cation, B is a divalent cation, and X is a monovalent anion) and structures similar thereto (hereinafter referred to as "perovskite compounds") as photoelectric conversion materials. However, it has been reported that perovskite compounds have high ionic crystallinity and are prone to ion migration. In particular, iodine anions constituting the X site are prone to migration, and when an internal electric field is generated in a solar cell device under light irradiation, they move toward the hole transport layer side. For example, Non-Patent Document 2 reports that iodine ions that move to the hole transport layer side when a positive bias is applied reduce the hole transport material 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene (hereinafter referred to as "Spiro-OMeTAD"). When the hole transport layer is reduced and the hole concentration decreases, the hole extraction and hole transport capabilities decrease, resulting in a decrease in the performance of the solar cell device.

[0009] In order to solve this problem, the present inventors have considered increasing the hole concentration of the hole transport material in advance and reducing the diffusion of iodine ions into holes so that the hole concentration of the hole transport layer does not decrease significantly even if migration of iodine anions occurs. In order to increase the hole concentration of the hole transport material, it is advisable to add an oxidizing agent having an oxidation-reduction potential capable of oxidizing the hole transport material.

[0010] In this disclosure, "oxidizing agent" also includes Lewis acids that can accept electrons from a hole transport material and increase the hole concentration in the hole transport material.

[0011] For example, fluoroboron-based compounds such as tris(pentafluorophenyl)borane (hereinafter referred to as "TPFPB") and its derivatives have a sufficiently high redox potential, and therefore can increase the hole concentration of almost all hole transport materials that are compatible with the electronic level of perovskite solar cells. In addition, in order to prevent the diffusion of iodine anions, it is possible to provide an intermediate layer between the perovskite photoelectric conversion layer and the hole transport layer. In the past, alkylammonium iodide or phenylalkylammonium iodide has been widely used in this intermediate layer for the purpose of passivating defects on the perovskite surface (see Non-Patent Documents 3 and 4). However, when these iodine-based materials are used, the fluoroboron-based compounds react with iodine, and the hole concentration of the hole transport material cannot be sufficiently increased. Therefore, the present inventors have found that by adding a fluoroboron-based compound to the hole transport layer and providing an intermediate layer containing at least one selected from the group consisting of bromides, chlorides, and fluorides as an iodine anion diffusion prevention layer, the redox reaction in the hole transport layer operates as designed even during light irradiation, and light durability is greatly improved. Table 1 shows a schematic diagram of the redox reaction in the hole transport layer that occurs during light irradiation when poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter referred to as "PTAA") is used as the hole transport material. Note that Table 1 shows a case where bromide is used as at least one example selected from the group consisting of bromides, chlorides, and fluorides for the intermediate layer. As described above, unlike the conventional idea centered on conversion efficiency, by focusing on light durability and the redox potential of the constituent components, it has been found that unexpected combinations are effective. [Table 1]

[0012] First Embodiment The solar cell according to the first embodiment will be described below. The solar cell according to the first embodiment has: A first electrode, a photoelectric conversion layer, an intermediate layer, a hole transport layer, and a second electrode, in this order, the hole transport layer comprises a hole transport material and an oxidant; The photoelectric conversion layer contains a perovskite compound containing iodine, and The intermediate layer includes at least one selected from the group consisting of bromide, chloride, and fluoride.

[0013] With the above configuration, the solar cell according to the first embodiment has high light durability.

[0014] The perovskite solar cell according to the first embodiment may include a substrate. Figure 1 shows a cross-sectional view of the solar cell according to the first embodiment.

[0015] The solar cell 100 shown in FIG. 1 includes a substrate 1, a first electrode 2, a photoelectric conversion layer 3, an intermediate layer 4, a hole transport layer 5, and a second electrode 6, in this order.

[0016] The perovskite solar cell of the present disclosure may include an electron transport layer between the first electrode and the photoelectric conversion layer. Figure 2 shows a cross-sectional view of a modified example of the solar cell according to the first embodiment.

[0017] The solar cell 200 shown in FIG. 2 includes a substrate 1, a first electrode 2, an electron transport layer 7, a photoelectric conversion layer 3, an intermediate layer 4, a hole transport layer 5, and a second electrode 6, in this order.

[0018] The perovskite solar cell according to the first embodiment may include a porous layer. Figure 3 shows a cross-sectional view of a modified example of the solar cell according to the first embodiment.

[0019] The solar cell 300 shown in FIG. 3 comprises a substrate 1, a first electrode 2, an electron transport layer 7, a porous layer 8, a photoelectric conversion layer 3, an intermediate layer 4, a hole transport layer 5, and a second electrode 6, in this order.

[0020] The solar cell 300 is fabricated, for example, by the following method.

[0021] First, the first electrode 2 is formed on the surface of the substrate 1 by chemical vapor deposition (CVD), sputtering, or the like. Next, the electron transport layer 7 is formed on the first electrode 2 by sputtering, or the like. On the electron transport layer 7, the porous layer 8 is formed by coating, or the like. Then, the photoelectric conversion layer 3 is formed on the porous layer 8 by coating, or the like. Then, the intermediate layer 4 is formed on the photoelectric conversion layer 3 by coating, or the like. On the intermediate layer 4, the hole transport layer 5 is formed by coating, or the like. On the hole transport layer 5, the second electrode 6 is formed by CVD, sputtering, or the like, to obtain the solar cell 300. The solar cell 100 can be manufactured by the same method as the solar cell 300, except that the electron transport layer 7 and the porous layer 8 are not formed. The solar cell 200 can be manufactured by the same method as the solar cell 300, except that the porous layer 8 is not formed.

[0022] <Second embodiment> The solar cell according to the second embodiment will be described below. The matters described in the second embodiment will be omitted as appropriate.

[0023] The solar cell according to the second embodiment has: A first electrode, a photoelectric conversion layer, an intermediate layer, a hole transport layer, and a second electrode, in this order, the hole transport layer comprises a hole transport material and an oxidant; The photoelectric conversion layer contains a perovskite compound containing iodine, and The absolute value of the oxidation-reduction potential required for the cationized hole transport material to become neutral is greater than the absolute value of the oxidation-reduction potential required for the anions generated when the intermediate layer is ionized to become neutral.

[0024] With the above configuration, the solar cell according to the second embodiment has high light durability.

[0025] When the intermediate layer satisfies the above-mentioned structure, the hole transport material can be prevented from being reduced by the anions contained in the intermediate layer.

[0026] The redox potential can be measured, for example, by inserting a standard electrode (eg, platinum) and a reference electrode into an aqueous solution in which a material whose redox potential is to be determined is dissolved, and reading the resulting potential difference.

[0027] If the intermediate layer contains, for example, C2H5NH3Br, the anion generated when the intermediate layer is ionized is Br - (i.e., bromine anion). Br - The redox potential at which the reaction of the following formula (1) occurs is approximately 5.7 eV. Note that this redox potential is a value when the standard redox potential of hydrogen is 4.6 eV. Br - →Br+e - (1)

[0028] Each component of the solar cell of the present disclosure will be specifically described below.

[0029] <Substrate 1> The substrate 1 holds each layer of the solar cell. The substrate 1 can be made of a transparent material. For example, a glass substrate or a plastic substrate (including a plastic film) can be used. If the first electrode 2 has sufficient strength, the first electrode 2 can hold each layer, and therefore the substrate 1 does not need to be provided.

[0030] <1st electrode 2> The first electrode 2 has electrical conductivity. The first electrode 2 may also have light-transmitting properties. For example, the first electrode 2 transmits light from the visible region to the near infrared region. The first electrode 2 may be made of, for example, a transparent and electrically conductive metal oxide. Examples of such metal oxides include: (i) indium-tin composite oxide, (ii) antimony-doped tin oxide; (iii) fluorine-doped tin oxide; (iv) zinc oxide doped with at least one element selected from the group consisting of boron, aluminum, gallium, and indium; or (v) A combination of these It is.

[0031] The first electrode 2 may be formed by using a non-transparent material and providing a light-transmitting pattern. Examples of the light-transmitting pattern include a line (striped), wavy, lattice (i.e., mesh), or punched metal pattern in which a large number of fine through-holes are regularly or irregularly arranged. When the first electrode 2 has such a pattern, light can be transmitted through the portion where the electrode material is not present. Examples of the non-transparent material are platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, or an alloy containing any of these. A conductive carbon material may be used as the non-transparent material.

[0032] When the solar cell does not include the electron transport layer 7, the first electrode 2 has a blocking property against holes from the photoelectric conversion layer 3. In this case, the first electrode 2 does not make ohmic contact with the photoelectric conversion layer 3. Furthermore, the blocking property against holes from the photoelectric conversion layer 3 means a property of passing only electrons generated in the photoelectric conversion layer 3 and not passing holes. The Fermi energy level of a material having such a property is higher than the energy level of the upper end of the conduction band of the photoelectric conversion layer 3. The Fermi energy level of a material having such a property may be higher than the Fermi energy level of the photoelectric conversion layer 3. A specific example of the material is aluminum. Aluminum does not have light-transmitting properties. Therefore, when forming a light-transmitting electrode using aluminum, for example, an electrode having the above-mentioned pattern shape is adopted.

[0033] When the solar cell includes an electron transport layer 7 between the first electrode 2 and the photoelectric conversion layer 3, the first electrode 2 does not need to have a blocking property for holes from the photoelectric conversion layer 3. In this case, the first electrode 2 may be made of a material capable of forming an ohmic contact with the photoelectric conversion layer 3. In this case, the first electrode 2 may or may not be in ohmic contact with the photoelectric conversion layer 3.

[0034] The light transmittance of the first electrode 2 may be, for example, 50% or more, or 80% or more. The wavelength of light that the first electrode 2 should transmit depends on the absorption wavelength of the photoelectric conversion layer 3.

[0035] The first electrode 2 may have a thickness of, for example, 1 nm or more and 1000 nm or less.

[0036] <Electron transport layer 7> The electron transport layer 7 includes a semiconductor. The electron transport layer 7 is desirably formed of a semiconductor having a band gap of 3.0 eV or more. This allows visible light and infrared light to transmit to the photoelectric conversion layer 3. Examples of the semiconductor are an organic n-type semiconductor or an inorganic n-type semiconductor.

[0037] Examples of organic n-type semiconductors are imide compounds, quinone compounds, fullerenes or fullerene derivatives. Examples of inorganic n-type semiconductors are metal oxides or perovskite oxides. Examples of metal oxides are oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga or Cr. Examples of metal oxides are TiO2. Examples of perovskite oxides are SrTiO3 or CaTiO3.

[0038] The electron transport layer 7 may contain a material having a band gap larger than 6 eV. Examples of materials having a band gap larger than 6 eV include: (i) Alkali metal or alkaline earth metal halides, such as lithium fluoride or calcium fluoride; (ii) an oxide of an alkaline earth metal, such as magnesium oxide; or (iii) Silicon dioxide In this case, in order to ensure the electron transporting property of the electron transport layer 7, the electron transport layer 7 may have a thickness of, for example, 10 nm or less.

[0039] The electron transport layer 7 may include a plurality of layers made of different materials.

[0040] <Porous layer 8> The porous layer 8 is disposed, for example, between the photoelectric conversion layer 3 and the electron transport layer 7. The porous layer 8 can serve as a base when the photoelectric conversion layer 3 is formed on the electron transport layer 7. The porous layer 8 does not inhibit the light absorption of the photoelectric conversion layer 3 and the electron transfer from the photoelectric conversion layer 3 to the electron transport layer 7.

[0041] The porous layer 8 includes a porous body. The porous body includes pores. The pores included in the porous layer 8 are connected from the portion in contact with the electron transport layer 7 to the portion in contact with the photoelectric conversion layer 3. The pores are typically filled with a material constituting the photoelectric conversion layer 3, and electrons can move directly from the photoelectric conversion layer 3 to the electron transport layer 7.

[0042] The porous body is formed, for example, by a series of insulating or semiconducting particles. Examples of insulating particles are aluminum oxide particles or silicon oxide particles. Examples of semiconducting particles are inorganic semiconductor particles. Examples of inorganic semiconductors are metal oxides, perovskite oxides of metal elements, sulfides of metal elements, or metal chalcogenides. Examples of metal oxides are oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si, or Cr. Examples of metal oxides are TiO2. Examples of perovskite oxides of metal elements are SrTiO3 or CaTiO3. Examples of sulfides of metal elements are CdS, ZnS, In2S3, PbS, Mo2S, WS2, Sb2S3, Bi2S3, ZnCdS2, or Cu2S. Examples of metal chalcogenides are CdSe, In2Se3, WSe2, HgS, PbSe, or CdTe.

[0043] The thickness of the porous layer 8 may be 0.01 μm or more and 10 μm or less, or 0.1 μm or more and 1 μm or less. The porous layer 8 may have a large surface roughness. Specifically, the surface roughness coefficient given by the value of effective area / projected area may be 10 or more, or may be 100 or more. The projected area is the area of ​​a shadow that is cast behind an object when the object is illuminated with light from the front. The effective area is the actual surface area of ​​the object. The effective area can be calculated from the volume obtained from the projected area and thickness of the object, and the specific surface area and bulk density of the material that constitutes the object.

[0044] The solar cell of the present disclosure does not necessarily include the porous layer 8.

[0045] <Photoelectric conversion layer 3> The photoelectric conversion layer 3 includes a perovskite compound represented by the composition formula ABX3. A is a monovalent cation. Examples of the cation A are monovalent cations such as alkali metal cations or organic cations. More specifically, methylammonium cation (CH3NH3 + ), formamidinium cation (NH2CHNH2 + ), Cesium cation (Cs + ) are included. B is a divalent metal cation. Examples of cation B are Pb cation, Sn cation, or Ge cation. X is a monovalent anion and includes iodine. Examples of anion X are halogen anions. Each site of cation A, cation B, and anion X may be occupied by multiple types of ions.

[0046] The thickness of the photoelectric conversion layer 3 depends on the level of light absorption, but is, for example, 100 nm to 2000 nm. The photoelectric conversion layer 3 can be formed by using a solution coating method or the like.

[0047] <Middle layer 4> The intermediate layer 4 functions as a diffusion prevention layer for preventing iodine anions from the photoelectric conversion layer 3 to the hole transport layer 5 .

[0048] Bromine, chlorine, and fluorine have sufficiently high oxidation-reduction potentials and therefore do not inhibit the oxidation of the hole transport material by the oxidizing agent in the hole transport layer 5. As a result, the solar cell has high light durability.

[0049] For example, it is desirable that the rate of change in efficiency of a solar cell is within 0.2% / h, i.e., between −0.2% / h and 0.2% / h. Here, the rate of change in efficiency is defined as the rate of change in efficiency when the solar cell is charged to 100 mW / cm 2 This is the rate of change in photoelectric conversion efficiency per unit time when the device is irradiated with simulated sunlight.

[0050] In order to improve the light durability of the solar cell, the intermediate layer 4 may contain at least one selected from the group consisting of bromide, chloride, and fluoride as a main component. Here, the main component refers to a component that is contained in the largest amount in terms of molar ratio. The intermediate layer 4 may be substantially composed of at least one selected from the group consisting of bromide, chloride, and fluoride. Here, "the intermediate layer 4 is substantially composed of at least one selected from the group consisting of bromide, chloride, and fluoride" means that the total content of bromide, chloride, and fluoride in the intermediate layer 4 is 90 mol% or more. The content may be 95 mol% or more. The intermediate layer 4 may be composed of only at least one selected from the group consisting of bromide, chloride, and fluoride.

[0051] In order to increase the light durability of the solar cell, the intermediate layer 4 may contain bromide. The intermediate layer 4 may consist essentially of bromide. Here, "the intermediate layer 4 consists essentially of bromide" means that the intermediate layer 4 contains 90 mol % or more of bromide. The intermediate layer 4 may contain 95 mol % or more of bromide. The intermediate layer 4 may consist only of bromide.

[0052] In order to improve the light durability of the solar cell, the intermediate layer 4 may contain a compound represented by the formula R-NH4X, where R is a hydrocarbon group and X is at least one selected from the group consisting of bromine, chlorine, and fluorine. Examples of R are an alkyl group, a phenyl group, or a phenylalkyl group. X may contain bromine.

[0053] R may be an alkyl group. That is, the bromide may be an alkylammonium bromide. In order to sufficiently ensure the diffusion prevention performance of the iodine anion, the alkylammonium bromide may have 4 or more carbon atoms.

[0054] In order not to impede charge injection, the thickness of the intermediate layer 4 may be 10 nm or less.

[0055] <Hole transport layer 5> The hole transport layer 5 includes a hole transport material and an oxidizing agent. The oxidizing agent is added to increase the concentration of holes.

[0056] The hole transport material may include a triphenylamine derivative.

[0057] Examples of triphenylamine derivatives are spiro-OMeTAD, a spiro-OMeTAD derivative, PTAA, or a PTAA derivative.

[0058] As the spiro-OMeTAD derivative, at least a part of the hydrogen atoms or methoxy groups of spiro-OMeTAD may be replaced with another functional group. For example, at least a part of the methoxy groups of spiro-OMeTAD may be replaced with hydrogen atoms or methyl groups. Alternatively, at least a part of the hydrogen atoms of spiro-OMeTAD may be replaced with methyl groups or methoxy groups.

[0059] As the PTAA derivative, at least a part of the hydrogen atoms or methyl groups of PTAA may be replaced with another functional group. For example, at least a part of the methyl groups of PTAA may be replaced with hydrogen atoms or methoxy groups. Alternatively, at least a part of the hydrogen atoms of PTAA may be replaced with methyl groups or methoxy groups.

[0060] The triphenylamine derivative may be PTAA or a PTAA derivative.

[0061] The hole transport layer 5 may contain not only triphenylamine derivatives but also other hole transport materials. Examples of hole transport materials are organic or inorganic semiconductors.

[0062] Examples of organic materials used as hole transport materials include poly(3-hexylthiophene-2,5-diyl) (hereinafter referred to as "P3HT") or poly(3,4-ethylenedioxythiophene) (hereinafter referred to as "PEDOT"). In particular, it may be a phenylamine having an electronic level suitable for perovskite solar cells. The molecular weight is not particularly limited, but it may be a polymer.

[0063] Examples of inorganic semiconductors used as hole transport materials are Cu2O, CuGaO2, CuSCN, CuI, CuPC, and NiO. x , MoO x , V2O5, or carbon-based materials such as graphene oxide.

[0064] The oxidizing agent may be a fluoroboron-based compound, which has high stability and a suitable redox potential for oxidizing the hole transport material.

[0065] The fluoroboron-based compound is, for example, a boron compound having a pentafluorophenyl group. Examples of such compounds are TPFPB, 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate, or N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate.

[0066] The fluoroboron-based compound may be TFPPB or a TFPPB derivative.

[0067] The oxidizing agent may be tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III) tri[bis(trifluoromethane)sulfonimide] (i.e., FK209Co(III)TFSI salt).

[0068] The oxidizing agent may be a salt containing NO. Examples of such salts are NO-TFSI, NO-BF4, NO-PF6, or TEMPO-TFSI.

[0069] The oxidizing agent may be 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (i.e., F4-TCNQ).

[0070] The hole transport layer 5 may include a plurality of layers formed from different materials.

[0071] From the viewpoint of low resistance, the thickness of the hole transport layer 5 may be 1 nm or more and 1000 nm or less, or may be 10 nm or more and 500 nm or less.

[0072] Examples of the method for forming the hole transport layer 5 include a coating method or a printing method. Examples of the coating method include a doctor blade method, a bar coating method, a spray method, a dip coating method, or a spin coating method. An example of the printing method is a screen printing method. The hole transport layer 5 may be formed by pressing or baking a film obtained by mixing a plurality of materials. When the hole transport material is a low-molecular organic material or an inorganic semiconductor, the hole transport layer 5 may be formed by a vacuum deposition method.

[0073] The hole transport layer 5 may contain a supporting electrolyte and a solvent. The supporting electrolyte and the solvent have the effect of stabilizing holes in the hole transport layer 5.

[0074] Examples of supporting electrolytes are ammonium salts or alkali metal salts. Examples of ammonium salts are tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazolium salts, or pyridinium salts. Examples of alkali metal salts are LiN(SO2CnF 2n+1 )2, LiPF6, LiBF4, lithium perchlorate, or potassium boron tetrafluoride.

[0075] The solvent contained in the hole transport layer 5 may have high ionic conductivity. The solvent may be either an aqueous solvent or an organic solvent. From the viewpoint of stabilizing the solute, the solvent may be an organic solvent. Examples of the organic solvent include heterocyclic compounds such as tert-butylpyridine (hereinafter referred to as "tBP"), pyridine, or n-methylpyrrolidone.

[0076] Ionic liquids may be used as solvents either alone or in combination with other solvents. Ionic liquids have low volatility and high flame retardancy.

[0077] Examples of ionic liquids are imidazolium compounds such as 1-ethyl-3-methylimidazolium tetracyanoborate, pyridine compounds, cycloaliphatic amine compounds, aliphatic amine compounds, or azonium amine compounds.

[0078] <Second electrode 6> Since the solar cell of the present disclosure has the hole transport layer 5, the second electrode 6 does not need to have blocking properties against electrons from the photoelectric conversion layer 3. In other words, the material constituting the second electrode 6 may be a material that forms ohmic contact with the photoelectric conversion layer 3.

[0079] The second electrode 6 has electrical conductivity. The second electrode 6 may have light-transmitting properties. The second electrode 6 is configured in the same manner as the first electrode 2.

[0080] Of the first electrode 2 and the second electrode 6, it is sufficient that the electrode on the side where light is incident has light-transmitting properties. Therefore, one of the first electrode 2 and the second electrode 6 does not have to have light-transmitting properties. In other words, one of the first electrode 2 and the second electrode 6 does not have to use a material having light-transmitting properties, and does not have to have a pattern including openings that transmit light. EXAMPLES

[0081] Hereinafter, the present disclosure will be described in more detail with reference to examples.

[0082] The solar cell according to the first embodiment has a structure similar to that of the solar cell 300 shown in Fig. 3. The components are as follows. Substrate 1: Glass substrate First electrode 2: Indium-doped SnO2 layer (surface resistance 10Ω / sq., manufactured by Geomatec) Electron transport layer 7: TiO2 (thickness: 10 nm, manufactured by Geomatec) Porous layer 8:TiO2 Photoelectric conversion layer 3: Mainly contains CH(NH2)PbI3 Intermediate layer 4: C2H5NH3Br Hole transport layer 5: Contains PTAA (manufactured by Aldrich) as a hole transport material and TPFPB (manufactured by Tokyo Chemical Industry) as an additive. Second electrode 6: gold (thickness: 80 nm)

[0083] The solar cell according to Example 1 was fabricated as follows.

[0084] A 1 mm-thick conductive glass substrate (manufactured by Nippon Sheet Glass) on which an indium-doped SnO2 layer and a TiO2 layer were formed was used as the substrate 1, the first electrode 2, and the electron transport layer 7. A solution of titanium oxide nanoparticle paste (150 mg) (NR-D30, manufactured by Greatcell Solar) diluted with ethanol (1 mL) was applied by spin coating onto the TiO2 layer, and then baked at 500°C for 30 minutes. In this way, a porous layer 8 was formed.

[0085] Next, a solution containing PbI2 (0.92M, manufactured by Tokyo Chemical Industry Co., Ltd.), PbBr2 (0.17M, manufactured by Tokyo Chemical Industry Co., Ltd.), FAI (0.83M, manufactured by Greatcell Solar Co., Ltd.), MABr (0.17M, manufactured by Greatcell Solar Co., Ltd.), CsI (0.05M, manufactured by Iwatani Corporation), and RbI (0.05M, manufactured by Iwatani Corporation) was prepared. The solvent of the solution was a mixture of dimethyl sulfoxide (DMSO, manufactured by acros Co., Ltd.) and N,N-dimethylformamide (DMF, manufactured by acros Co., Ltd.). The mixture ratio of DMSO and DMF in the solution was 1:4 by volume. This solution was spin-coated on the electron transport layer 7 and annealed on a hot plate at 100°C for 45 minutes to form a photoelectric conversion layer 3.

[0086] Next, a solution of IPA (1 mL) (manufactured by Acros Organics) containing C2H5NH3Br (1 mg) (manufactured by Greatcell Solar) was prepared. This solution was spin-coated onto the photoelectric conversion layer 3, thereby forming the intermediate layer 4.

[0087] Next, 1 mL of a toluene (manufactured by acros) solution containing PTAA (10 mg) and TFPPB (1.8 mg) was prepared. This solution was spin-coated on the intermediate layer 4 to form the hole transport layer 5.

[0088] Finally, gold (thickness: 80 nm) was evaporated onto the hole transport layer 5 to form a second electrode 6 .

[0089] In this manner, the solar cell according to Example 1 was obtained.

[0090] All the above steps were carried out in a dry room with a dew point below -40°C.

[0091] <Example 2> A solar cell according to Example 2 was obtained in the same manner as in Example 1, except that the solute of the solution for producing the intermediate layer 4 was C3H7NH3Br (manufactured by Greatcell Solar).

[0092] <Example 3> A solar cell according to Example 3 was obtained in the same manner as in Example 1, except that the solute of the solution for producing the intermediate layer 4 was C4H9NH3Br (manufactured by Greatcell Solar).

[0093] <Example 4> The solute of the solution for preparing the intermediate layer 4 is CH 17 A solar cell according to Example 4 was obtained in the same manner as in Example 1, except that NH3Br (manufactured by Greatcell Solar) was used.

[0094] <Comparative Example 1> A solar cell according to Comparative Example 1 was obtained in the same manner as in Example 1, except that the intermediate layer 4 was not formed and TFPPB was not added to the hole transport layer 5.

[0095] <Comparative Example 2> The hole transport layer 5 was produced without forming the intermediate layer 4 as follows. A solution was prepared by mixing a toluene (manufactured by acros) solution (1 mL) containing PTAA (10 mg), tBP (6 μL), and an acetonitrile solution (4.8 μL) in which LiTFSI was dissolved at a concentration of 1.8 M. The hole transport layer 5 was formed by spin-coating this solution on the intermediate layer 4.

[0096] A solar cell according to Comparative Example 2 was obtained in the same manner as in Example 1, except for the above points.

[0097] <Comparative Example 3> A solar cell according to Comparative Example 3 was obtained in the same manner as in Example 1, except that the intermediate layer 4 was not formed.

[0098] <Comparative Example 4> The hole transport layer 5 was fabricated as follows. A solution was prepared by mixing a toluene (manufactured by acros) solution (1 mL) containing PTAA (10 mg), tBP (6 μL), and an acetonitrile solution (4.8 μL) in which LiTFSI was dissolved at a concentration of 1.8 M. The hole transport layer 5 was formed by spin-coating this solution on the intermediate layer 4.

[0099] A solar cell according to Comparative Example 4 was obtained in the same manner as in Example 3, except for the above points.

[0100] <Comparative Example 5> A solar cell according to Comparative Example 5 was obtained in the same manner as in Example 1, except that the solute of the solution for producing the intermediate layer 4 was C4H9NH3I (manufactured by Greatcell Solar).

[0101] [Evaluation of solar cell characteristics] The characteristics of the solar cells of Examples 1 to 4 and Comparative Examples 1 to 5 were measured using a solar simulator (ALS440B, manufactured by BAS) at 100 mW / cm 2 The output was set to 1.2 V and evaluated under simulated sunlight. The output current value versus applied voltage was changed from 1.2 V to 0 V and recorded, and the conversion efficiency was calculated. Table 2 shows the initial efficiencies of the solar cells of Examples 1 to 4 and Comparative Examples 1 to 5.

[0102] [Percentage change in efficiency] A light irradiation test was carried out on the solar cells of Examples 1 to 4 and Comparative Examples 1 to 5. 2 A resistor was connected so that the solar cell device would operate near the optimal operating point under simulated sunlight, and the output was recorded by a data logger. The rate of change in photoelectric conversion efficiency per unit time was calculated by (photoelectric conversion efficiency after light irradiation test - photoelectric conversion efficiency before light irradiation test) / photoelectric conversion efficiency before light irradiation test / test time x 100 (% / h). The rates of change in photoelectric conversion efficiency of the solar cells of Examples 1 to 4 and Comparative Examples 1 to 5 are shown in Table 2.

[0103] [Table 2]

[0104] For stable operation of a solar cell, it is considered desirable that the efficiency change rate is within 2%. Although the stability time required by the industrial standard varies depending on the type of solar cell, the maximum operating time of a solar cell per day is approximately 10 hours as a guide. Therefore, it is desirable that the efficiency change rate per hour is within 0.2% / h, that is, the value calculated by the above formula for determining the change rate of the photoelectric conversion efficiency per unit time is -0.2% / h or more and 0.2% / h or less. It can be seen that the solar cells of Examples 1 to 4 have a decrease in the photoelectric conversion efficiency per unit time of 0.2% / h or less compared to the solar cells of Comparative Examples 1 to 5. Therefore, a solar cell having an intermediate layer containing at least one selected from the group consisting of bromides, chlorides, and fluorides, and a hole transport layer containing a fluoroboron-based compound as an additive, has excellent light durability. As can be seen from the results of the solar cells of Examples 3 and 4, when the carbon number of the bromide contained in the intermediate layer is 4 or more, no decrease in the photoelectric conversion efficiency per unit time was confirmed. Therefore, when the carbon number of the bromide contained in the intermediate layer is 4 or more, the solar cell has even better light durability.

[0105] [Evaluation of the rate of change of iodine anion] The rate of change in iodine anion before and after the light irradiation test of the solar cells of Example 3 and Comparative Example 3 was measured using hard X-ray photoelectron spectroscopy (HAXPES).

[0106] The peak integral intensity (I 0 ) and the peak integral intensity of monovalent iodine (i.e., iodine anion) (I - ) was measured.

[0107] The proportion of zero-valent iodine is I 0 / (I 0 +I - ) × 100.

[0108] The rate of change of iodine anion was calculated by (proportion of zero-valent iodine after light irradiation test−proportion of zero-valent iodine before light irradiation test) / proportion of zero-valent iodine before light irradiation test×100(%).

[0109] The change rate of iodine anion in the solar cell of Example 3 was -1.9%. The change rate of iodine anion in the solar cell of Comparative Example 3 was +9.6%. Therefore, in the solar cell having an intermediate layer containing bromide and a hole transport layer containing a fluoroboron-based compound as an additive, the amount of change of iodine anion to zero-valent iodine is smaller than that in the solar cell having a hole transport layer containing a fluoroboron-based compound as an additive but not having an intermediate layer. From the above results, it is considered that the reduction of the hole transport material by iodine anion is suppressed in the solar cell having an intermediate layer containing bromide and a hole transport layer containing a fluoroboron-based compound as an additive. In this way, it was confirmed that the light durability is improved by the oxidation-reduction reaction in the hole transport layer operating as designed. [Industrial Applicability]

[0110] The solar cells of the present disclosure can be used in a variety of applications, including traditional solar cell applications. [Explanation of symbols]

[0111] 1 Board 2 1st electrode 3 Photoelectric conversion layer 4. Middle Tier 5. Hole transport layer 6 Second electrode 7 Electron transport layer 8 Porous layer 100, 200, 300 solar cells

Claims

1. A first electrode, a photoelectric conversion layer, an intermediate layer, a hole transport layer, and a second electrode, in this order; Where: the hole transport layer comprises a hole transport material and an oxidant; The photoelectric conversion layer contains a perovskite compound containing iodine, and The intermediate layer contains 90 mol % or more of bromide, The bromide is an alkylammonium bromide. Solar cell.

2. The hole transport material comprises a triphenylamine derivative. The solar cell according to claim 1 .

3. The triphenylamine derivative is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] or a poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] derivative. The solar cell according to claim 2 .

4. The oxidizing agent is a fluoroboron-based compound. The solar cell according to claim 1 .

5. The fluoroboron-based compound is tris(pentafluorophenyl)boran or a tris(pentafluorophenyl)boran derivative; The solar cell according to claim 4 .

6. The alkyl ammonium bromide has 4 or more carbon atoms. The solar cell according to claim 1 .

Citation Information

Patent Citations

  • Inversion perovskite solar cell containing alkali metal halide hole modification layer and preparation method thereof

    CN111223990A

  • Method of manufacturing organic electroluminescent element

    JP2014220248A

  • Solar cell and method of manufacturing the same

    JP2016051891A

  • Photoelectric conversion element

    JP2018085497A

  • Method for manufacturing photoelectric conversion element

    JP2019071500A